Antimicrobial Activity of Ethanol Extract of Rhizome Turmeric (Curcuma Longa L.) For Growth of Escherichia coli, Staphylococcus aureus and Candida albicans - Kasta, Gurning (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study was to determine at what concentration of ethanol extract of rhizome turmeric is active against Escherichia coli, Staphylococcus aureus and Candida albicans. Methods: Ethanolic extract of rhizome turmeric was tested for phytochemical screening by using standard protocol. Antimicrobial testing was using the diffusion disc method to measure the inhibition zone against the Escherichia coli, Staphylococcus aureus and Candida albicans with various concentration of rhizome turmeric extract (500 mg/mL, 400 mg/mL, 300 mg/mL, 200 mg/mL, 100 mg/mL, 50 mg/mL, 25 mg/mL). Results: Phytochemical screening showed that ethanolic extract of rhizome turmeric contain alkaloids, flavonoids, saponins, tannins, and triterpenoid/steroid. The antimicrobial inhibition of ethanol extract of rhizome turmeric against Escherichia coli, Staphylococcus aureus and Candida albicans microbia at a concentration of 500 mg/mL had a diameter of 15.7 mm, 15 mm and 15.18 mm with a strong category. Conclusions: rhizome turmeric could be use as a novel antimicrobial agent.